Healthy eating rules for young teenagers (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
It is very important to talk about the rules of proper nutrition for young teenagers, because young teenagers have actively developing organisms, proper nutrition provides them with energy and new information it is very important for them to get This article examines the scientific evidence for healthy eating habits for young teens.